Fractional order breast cancer model with therapy, prevention diagnosis and optimal control based on real data - Shaimaa A. M. Abdelmohsen; Haifa A. Alyousef; Sayed Saifullah (Scientific Reports)
Abstract Cancer is one of the most perilous diseases worldwide, often incurable if not diagnosed in its early stages. Among cancers, breast cancer ranks as the second most lethal, particularly affecting women and contributing to a significant number of fatalities. This work analyzes the breast cancer model in the fractional scenario by incorporating the therapy and prevention diagnosis. The model is subjected to theoretical and numerical investigations to explore the dynamics and predictions of the disease. Furthermore, optimal disease control is presented along with a sensitivity analysis of model parameters. Furthermore, the obtained results are compared with the real data with varying fractional orders, revealing that most of the data points coincide with the fractional order 0.98.